2013
DOI: 10.1007/s12032-012-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pattern, time and risk factors influencing recurrence in triple-negative breast cancer patients

Abstract: The aim of the study was to assess the rate, pattern, and time of recurrence in patients with triple-negative breast cancer (TNBC) and to evaluate factors influencing recurrence and overall survival in this group of patients. Out of 2,534 consecutive breast cancer patients diagnosed between January 2005 and December 2006, 228 (9 %) were TNBC (ER/PR/HER2-negative). The clinicopathological characteristics were determined using descriptive statistics. The overall survival (OS) and disease-free survival (DFS) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 33 publications
(52 reference statements)
10
98
3
7
Order By: Relevance
“…24 The period of highest risk of recurrence within the first three years after the primary treatment was identified by other researchers who also reported that the brain and lungs (15.0% and 14.0%, respectively) are the most common sites for metastasis. 22 In contrast, we verified in this study that bones and the lungs (35.5% and 25.3%, respectively) were the most common sites for recurrence.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…24 The period of highest risk of recurrence within the first three years after the primary treatment was identified by other researchers who also reported that the brain and lungs (15.0% and 14.0%, respectively) are the most common sites for metastasis. 22 In contrast, we verified in this study that bones and the lungs (35.5% and 25.3%, respectively) were the most common sites for recurrence.…”
Section: Discussionsupporting
confidence: 42%
“…25 According to a study conducted with patients cared for by a Cancer Center and Oncology Institute in Warsaw, Poland, survival rates were different depending on the site of metastasis; shorter length of survival was observed in cases of liver metastasis (3.5 months) and higher survival for lung metastasis (9.8 months) and local recurrence (9 months). 22 In this study, the highest occurrence of metastasis (25.2%) in a five-year period was verified between 2008 and 2013 in Goiania-GO, compared with 10.20% for distance metastasis in the same city in the period from 1989 to 2003. 26 This increase may be explained by technological advancements that facilitated the identification of breast cancer recurrence over the years.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Os carcinomas de mama TN têm um padrão característico de recorrência e metástase tumoral. Em estudo realizado com 228 pacientes diagnosticadas com câncer de mama TN, um terço apresentou doença metastática 19 , valor menor do que o encontrado em nosso estudo (52%). O risco de recidiva foi fortemente associado ao câncer de mama TN, colaborando para predizer seu pior prognóstico 20 .…”
Section: Discussionunclassified
“…6,7 The most vulnerable time period for early recurrence in TNBC is first three years after initial treatment with survival rate shorter than in non-TNBC patients. 8 However, there have been recent advancements on novel signalling pathways in the treatment of TNBC patients giving rise to novel chemotherapeutic approaches mostly focusing nano based solution that actively target this particular tumor. Use of agents targeting aberrant DNA repair is under clinical investigation showing a promising result improving the prognosis of the disease.…”
Section: Introductionmentioning
confidence: 99%